STRATEGI ACTIVE LEARNING DENGAN MODEL JIGSAW DALAM PEMBELAJARAN SKI DI SD/MI. - Khusnaini Hidayatul; Anik Faridah; Julaikha Noor Hasanah; Ahmad Hasan Yusuf (CV. Denasya Smart Publisher, 2026)
This study aims to describe the effectiveness of the active learning strategy through the jigsaw model in teaching Islamic Cultural History (SKI) at elementary and Islamic elementary schools. The research employed a library research method by reviewing relevant literature, including journals, theses, and previous studies. The findings indicate that the jigsaw model increases students’ activeness, responsibility, and critical thinking skills in understanding SKI material. Through the division of home groups and expert groups, students not only comprehend the material but also teach it to their peers and internalize Islamic moral values derived from historical events. This strategy also promotes collaboration and effective communication among students. Challenges such as limited time and differences in students’ abilities can be overcome through teacher guidance and the use of appropriate learning media. Therefore, the active learning strategy based on the jigsaw model is considered effective in creating interactive, enjoyable, and character-oriented SKI learning.